Renewable Energy, Green Finance, and Economic Growth in Morocco: Evidence from an ARDL Approach - Dahhou, Nabil; Bahetta, Soufiyan; Bouyghrissi , Soufiane; Kharbouch, Omar (International Journal of Energy Economics and Policy, 2025)
This paper investigates the relationship between green finance, renewable energy, and economic growth in Morocco, highlighting their roles in achieving sustainable development objectives. Morocco’s proactive approach, marked by the issuance of green bonds and the formulation of a national green taxonomy, aligns with global commitments to the Paris agreement and the Sustainable Development Goals. The study adopts the auto-regressive distributed Lag (ARDL) model to analyze quarterly data from 2016 to 2022, incorporating key variables such as green finance, foreign direct investment (FDI), renewable energy consumption, and greenhouse gas (GHG) emissions. The empirical findings indicate that while a 1% increase in green finance results in a modest 0.01% rise in GDP, renewable energy consumption demonstrates stronger short-term (0.29%) and long-term (0.36%) contributions to economic growth. Conversely, GHG emissions show a positive correlation with GDP, underscoring the ongoing reliance on carbon-intensive sectors despite efforts to transition to a green economy. The results emphasize the importance of robust regulatory frameworks, technological innovation, and public-private partnerships in maximizing the benefits of green finance and renewable energy investments. Addressing institutional barriers, improving market transparency, and fostering investor confidence through mechanisms such as green bonds and digital finance tools are critical to accelerating Morocco’s transition to a low-carbon economy. This study provides valuable insights for policymakers and stakeholders seeking to harmonize economic growth with environmental sustainability.